A tale of two Dickenses: Or, learning as fact, fiction and play. Issue 3 (2nd April 2022) - Rudrum, David
Over the years, a small industry has sprung up dedicated to preserving writers' homes and birthplaces, offering the chance to see first-hand the circumstances under which their key texts were written. Experiencing an insight into, say, Wordsworth's Dove Cottage, or Hardy's Wessex cottage, or the Bronte parsonage in Haworth, is widely held to be an educational experience, enhancing our appreciation of the link between the life and work of the author in question. Axiomatically – and simplistically – literary heritage sites like these might seem to offer the "truth" behind the "fiction", by showing the visitor the "real" world behind the "imaginative" writing. Thus, the educational experience they offer is often said to consist in providing an insight into context (historical/biographical, landscape and setting, etc.). This study sets out to challenge this assumption. As case studies, it will discuss two very (very!) different literary heritage sites: the Charles Dickens Birthplace Museum in Portsmouth and the now-defunct literary theme park Dickens World, which finally closed its doors in 2016. The former offers a biographical and historical interpretation of Dickens, ostensibly grounded in reality and truth – although the truth claims made for the museum are shown to be somewhat contestable. The latter appealed far more to the imagination, and to 'free play' with the text, than it did to truth. Obviously, these sites involve two completely different conceptions of what it is to provide an experience of literary education. The two are compared and contrasted, with passing reference to thinkers such as Roland Barthes, Michel Foucault, Kendall Walton and Mikhail Bakhtin, with a view to challenging and dismantling the commonsensical view that the educational value of literary heritage sites consists in revealing the truth behind the fiction.